EVALUASI STRUKTUR JEMBATAN BETON BERTULANG DENGAN METODE SNI 1725-2016 (STUDI KASUS JEMBATAN MARBALI JL.TUGU DOBO-DURJELA KABUPATEN KEPULAUAN ARU) - Suryani Maharani Saleh; Meriana Wahyu Nugroho (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The Aru Islands Regency, located in Maluku Province, covers an area of 6,426.77 km² and has a population of 102,237. One of the infrastructure initiatives being carried out by the local government is the construction of the Marbali Bridge. This study focuses on the use of reinforced concrete as the primary construction material for the bridge. It includes calculations of various technical aspects, such as loading according to SNI 1725-2016, with a moment capacity (Mu) control of ≥ p (BGT intensity), reinforcement and T-beam dimensions with an Rn control of < Rmax, and evaluation of deflection in the T-beam with a load combination control of δ ≤ δ Max. The results indicate that the ultimate moment (Mu) in the beam is 4,273 kN/m, and the ultimate shear force is 729.91 kN. The flexural reinforcement consists of 12 bars of D32 mm, while the shear reinforcement uses 2 bars of D12 mm for D13-100 mm stirrups. Accordingly, the calculation results conform to the established standards and the technical requirements needed for the construction of this bridge.